2020
DOI: 10.1007/s10909-020-02531-1
|View full text |Cite
|
Sign up to set email alerts
|

Specific Heat of Holmium in Gold and Silver at Low Temperatures

Abstract: The specific heat of dilute alloys of holmium in gold and in silver plays a major role in the optimization of low temperature microcalorimeters with enclosed $$^{163}{{\text {Ho}}}$$ 163 Ho , such as the ones developed for the neutrino mass experiment ECHo. We investigate alloys with atomic concentrations of $$x_{{{\text {Ho}}}}=0.01{-}4\%$$ x Ho = 0.01 - 4 % at temperatures between 10 and $$800\,{{{\hbox {mK}}}}$$ 800 mK . Due to the large total angular momentum $$J=8$$ J = 8 and nuclear spin … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…After the implantation process, a second host material layer with similar thickness is deposited before structuring the second absorber layer on top, which fully encloses the 163 Ho source. The host material of choice is silver, in order to lower the heat capacity contribution from the 163 Ho ions with respect to gold in the temperature range around 20 mK [14].…”
Section: Designmentioning
confidence: 99%
“…After the implantation process, a second host material layer with similar thickness is deposited before structuring the second absorber layer on top, which fully encloses the 163 Ho source. The host material of choice is silver, in order to lower the heat capacity contribution from the 163 Ho ions with respect to gold in the temperature range around 20 mK [14].…”
Section: Designmentioning
confidence: 99%
“…For the ECHo experiment the optimal activity has been determined to be 10 Bq per pixel which, combined with a time resolution of MMC well-below 1 µs would lead to an unresolved pile-up fraction well-below 10 −5 and, at the same time lead to an additional heat capacity of less than 50% of the one of gold absorber and Ag:Er sensor when the detectors are operated at a temperature of 20 mK. In [33] the specific heat per Ho atom in gold and silver has been measured as a function of Ho concentration and it was shown that for temperature above 100 mK the temperature dependence of the Ho specific heat follows that one measured for pure Ho samples, showing a Schottky anomaly at about 250 mK. This fact might induce some issues for the optimization of TES-based detector for the HOLMES experiment for which an activity of 300 Bq per pixel and an operational temperature around 80 mK are presently considered.…”
Section: Re Based Experimentsmentioning
confidence: 99%
“…For the ECHo experiment the optimal activity has been determined to be 10 Bq per pixel which, combined with a time resolution of MMCs well-below 1 s would lead to an unresolved pile-up fraction well-below 10 −5 . At the same time, such activity lead to an additional heat capacity of less than 50% of the one of the gold absorber and Ag:Er sensor, when the detectors are operated at a temperature of 20 mK [37].…”
Section: Ho Based Experimentsmentioning
confidence: 99%